Lipidomics analysis facilitate insight into the molecular mechanisms of urate nephropathy in a gout model induced by combination of MSU crystals injection and high-fat diet feeding - Hao, Guifeng; Xu, Xiaofen; Song, Jingyi; Zhang, Jida; Xu, Kejun (Frontiers in Molecular Biosciences, 2023)
Renal injury is one of the most common clinical manifestations of patients with hyperuricaemia/gout. The precise pathophysiological mechanism(s) for the renal injury is still unknown. Furthermore, it is also unclear whether the clinical therapies (e.g., colchicine and febuxostat) could prevent its progression or not. Lipids are involved in almost all of important biological processes and play critical roles in maintaining the renal functions. Herein, shotgun lipidomics was performed for class-targeted lipid analysis of cellular lipidomes in renal tissue of a gouty model induced by combination of monosodium urate crystals injection and high-fat diet feeding with/without treatment with either colchicine or febuxostat. Serum uric acid (UA), proinflammatory cytokines (i.e., TNF-α and IL-6), xanthine oxidase activity, footpad swelling, and pain threshold were determined to evaluate the gouty severity. Renal histopathological changes, blood urea nitrogen, creatinine, and kidney index were used to reflect renal injury. Lipidomics analysis revealed that altered triacylglycerol (TAG) profile, impaired mitochondrial function resulted by decreased tetra 18:2 cardiolipin, reduced 4-hydroxyalkenal (HNE) species, and elevated lysophospholipids were already present in the kidneys at early stage of renal injury, probably contributing to its occurrence and development. In addition to significantly reduce the UA level and relief the gouty severity, treatment with either colchicine or febuxostat could restore HNE bioavailability, thereby delaying the progression of renal injury. However, both of them could not recover the altered TAG profile and the impaired mitochondrial function, indicating that treatment with either of them could not completely prevent the development of renal injury in the gouty model.